IMPLEMENTASI EKSTRAKURIKULER SC (STUDENT COMPANY) DALAM MEMBENTUK JIWA WIRAUSAHA PESERTA DIDIK DI SMKN 2 BUDURAN KABUPATEN SIDOARJO - AMBARWATI, SELA (Inspirasi Manajemen Pendidikan, 2016)
Abstrak Pendidikan adalah sarana yang tepat untuk meningkatkan kualitas kehidupan pribadi dan masyarakat dalam menghadapi lingkungan yang semakin pesat mengalami perubahan, khususnya menghasilkan lulusan yang memiliki keunggulan dan mampu bersaing dalam situasi global. Pendidikan menjadi wahana yang tepat untuk membentuk karakter anak bangsa, khususnya pendidikan kewirausahaan dikarenakan saat ini Indonesia menghadapi Masyarakat Ekonomi Asean (MEA). Pendidikan kewirausahaan di SMKN 2 Buduran salah satunya di integrasikan melalui kegiatan ekstrakurikuler SC. Fokus dalam penelitian ini adalah (1) Bentuk kegiatan ekstrakurikuler SC dalam membentuk jiwa wirausaha peserta didik, (2) Organisasi pelaksana kegiatan ekstrakurikuler SC dalam membentuk jiwa wirausaha peserta didik, (3) Kendala-kendala yang ditemui pada kegiatan ekstrakurikuler SC dalam membentuk jiwa wirausaha peserta didik. Penelitian ini menggunakan pendekatan kualitatif dan menggunakan rancangan penelitian studi kasus. Teknik pengumpulan data yang digunakan yaitu teknik wawancara, observasi dan dokumentasi. Analisis data dalam penelitian ini menggunakan reduksi data, penyajian data dan penarikan kesimpulan. Sedangkan untuk keabsahan data peneliti menggunakan uji kredibilitas, tranferabilitas, dependabilitas, konfirmabilitas. Hasil penelitian ini menunjukkan bahwa (1) Bentuk kegiatan ekstrakurikuler SC mempunyai 10 aktivitas program yaitu: Briefing, Pembentukan organisasi, Analisa bisnis, Persiapan launching, Launching, Weekly meeting, Business Running, Personal action plan, Persiapan laporan akhir dan Likuidasi; (2) Organisasi pelaksana kegiatan ekstrakurikuler SC memiliki struktur organisasi yang didalamnya terdapat 13 jabatan beserta tugasnya, 13 jabatan tersebut meliputi: President, Vice President of Human Resources Development, Attandance and Payroll Specialist, Vice President of Marketing, Sales and Inventory Manager, Market Research Manager, Promotion Manager, Vice President of Finance, Vice President of Production, Production Manager, Quality Control and Product Development Manager, Vice President of Public Relations, Corporate Secretary; (3) Kendala-kendala yang ditemui pada kegiatan ekstrakurikuler SC yaitu terletak pada time manajemen, menyatukan pemikiran antar anggota perusahaan dan pada memasarkan produknya. Kata Kunci: implementasi, ekstrakurikuler SC, jiwa wirausaha, peserta didik. Abstract Education is the means by which the right to improve the quality of personal and community life in the face of increasingly rapid environmental change. Particularly to produce graduates who have the advantage and be able to compete in the global situasion. Education becomes a vehicle that is appropriate to form the character of the nation. Especially in entrepreneurship education because Indonesia is currently the ASEAN Economic Community (AEC). Entrepreneurship education at SMK 2 Buduran one integrated through extracurricular activities SC. The focus in this research are (1) the form of extracurricular activity Sc in Markowitz entrepreneurial spirit of students, (2) the organization to implement extracurricular Sc in shaping the entrepreneurial spirit of students, (3) constraints encountered in extracurricular activities Sc in shaping the entrepreneurial spirit participant learners. This research used a qualitative approach and use the draf case study research. Data collection techniques used are interview techniques, observation, and documention. Data analysis in this study uses the presentation data, data reduction, and withdrawal the conclusion. As for the validity of the data the researcher used the test of credibility, transferability, dependability, and confirmability. The results of this study indicate that (1) has the form of extracurricular activity SC 10 program activities, namely: Briefing, the establishment of organizations, business analysis, preparations for launching, launcing, weekly meetings, business running, personal action plan, preparation of the final report and liquidation; (2) the organization to implement extracurricular SC has an organizational structure in which there are 13 positions and their duties, 13 these positions include: President, Vice President of Human Resources Development, Attandance and Payroll Specialist, Vice President of Marketing, Sales and Inventory Manager, Market Research Manager, Promotion Manager, Vice President of Finance, Vice President of Production, Production Manager, Quality Control and Product Development Manager, Vice President of Public Relations, Corporate Secretary; (3) constraints encountered in extracurricular activities SC is located at the time as management, unify ideas among members and in marketing their products. Keywords:implementation, extracurriculas SC, entrepreneurial spirit, learners.